The battle against triple-negative breast cancer / Nur Syamimi Ariffin - Ariffin, Nur Syamimi (Faculty of Pharmacy, 2024)
Wildlife biologists say that wolf packs in the wild are not led by a domineering alpha male. “He’s just the father of the family,” says wolf researcher L. David Mech. That same belief lingers in triplenegative breast cancer (TNBC). It is the most aggressive subtype of breast cancer, mainly due to the lack of hormonal receptors for a targeted treatment. However, they are a sensitive subtype of breast cancer, hence it is their weakness that we can use to develop sensitization towards chemotherapy. In this case, low levels of drugs exposed to TNBC cells are likely to change their phenotypes, if not killing them, without triggering unnecessary side effects. Though this is speculative, there is a possibility, and we believe that it is encouraging, as the tricky part in treating TNBC patients is when the disease has spread to secondary organs. So far, there is no specific drugs that can efficiently target the metastatic breast cancer cells. Therefore, our team works on tackling this problem, one of which is to find a molecular protein that can specifically inhibit this particular phenotype from occurring in TNBC.